The Term Challenge in Social Media: A Lexicological Study - Afria, Rengki; Fardinal, Fardinal; Putri, Oktaviani Dwi (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
Challenge is a game that is rampant among social media users, especially in Indonesia. The purpose of this research is to find out the terms in the challenge by using the theory of terms in the study of lexicology. This research uses descriptive method with qualitative approach. The data in the study in the form of the results of the analysis of the challenge in terms of term studies with data sources derived from challenge circulating on social media. Data collection techniques were carried out using observation and documentation techniques. Presentation of data analysis results using qualitative analysis methods. There are seven challenges that will be analysed using the theory of lexicology study terms, namely: 10 years challenge, bottle cap challenge, vans challenge, age challenge, don't laugh challenge, baby shark challenge and chair challenge.